2017
DOI: 10.4187/respcare.05391
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Endotracheal Tube Scraping on Airway Resistance

Abstract: This study demonstrated that ETT scraping can reduce R. The decrease in R post-ETT scraping did not affect subsequent SBT success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…In the crossover study, despite a single outlier with an isolated large secretion bolus during one SSC suctioning event, the CSC device after a previous SSC suctioning period resulted in a significantly larger increase in secretion volume and secretion weight than with the SSC system. These are similar to results using other mechanical endotracheal tube cleaners [ 15 – 19 ]. Unlike these other systems, however, the CSC system is an integrated closed-suction system that does not require circuit disruption that could result in potential alveolar derecruitment and clinician exposure to pathogens.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the crossover study, despite a single outlier with an isolated large secretion bolus during one SSC suctioning event, the CSC device after a previous SSC suctioning period resulted in a significantly larger increase in secretion volume and secretion weight than with the SSC system. These are similar to results using other mechanical endotracheal tube cleaners [ 15 – 19 ]. Unlike these other systems, however, the CSC system is an integrated closed-suction system that does not require circuit disruption that could result in potential alveolar derecruitment and clinician exposure to pathogens.…”
Section: Discussionsupporting
confidence: 89%
“…Perhaps the most direct approach is to use mechanical devices to physically extract airway secretions out of the tube. First described using standard Fogarty catheters [14], more modern versions use a variety of catheter designs to physically "scrape" the inside of the ETT [15][16][17][18][19]. These devices generally enhance the efficiency of secretion clearance but, unfortunately, they are usually standalone catheters requiring circuit disruption for use and the need for a separate suction system.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchodilator administration may help differentiate reversible airway obstruction due to bronchospasm from fixed obstruction due to endotracheal tube occlusion. Because of the thick, highly viscous nature of secretions, we see a role for endotracheal tube cleaning devices in removing the debris, 30,31 particularly given the risk for respiratory decompensation and disease transmission that could occur during tube exchange or bronchoscopy. 23,25…”
Section: Discussionmentioning
confidence: 99%
“…82 A small randomized clinical trial showed lower ETT colonization and reduced biofilm thickness in the treatment group. 83 The clinical use of similar devices resulted in lower ETT resistance in vivo 84,85 and preserved ETT patency at extubation. 84,86 The use of the mucus shaver might also prevent the loss of antimicrobial activity of tube coatings, as demonstrated by preclinical data; however, a recent small clinical trial conducted with a similar cleaning device failed to show any benefit.…”
Section: Ett Cleaningmentioning
confidence: 98%